2023
DOI: 10.3390/microorganisms11040975
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Psychosocial Stress Is Associated with Reduced Diversity in the Early Infant Gut Microbiome

Abstract: The developing infant gut microbiome is highly sensitive to environmental exposures, enabling its evolution into an organ that supports the immune system, confers protection from infection, and facilitates optimal gut and central nervous system function. In this study, we focus on the impact of maternal psychosocial stress on the infant gut microbiome. Forty-seven mother–infant dyads were recruited at the HEAL Africa Hospital in Goma, Democratic Republic of Congo. Extensive medical, demographic, and psychosoci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
1

Year Published

2023
2023
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 67 publications
0
6
1
Order By: Relevance
“… 79 Furthermore, Flavonifractor plautii was negatively associated with maternal stress in samples obtained at 6 weeks, 3 months, and 6 months. 77 Rothia , with a slightly lower relative abundance in the SSC group, has been reported to be increased in formula-fed infants in two studies (one study found the opposite) 80 and to be negatively associated with childhood asthma. 81 Lastly, Eubacterium hallii , reclassified as Anaerobutyricum soehngenii , 82 was lower in the SSC group.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“… 79 Furthermore, Flavonifractor plautii was negatively associated with maternal stress in samples obtained at 6 weeks, 3 months, and 6 months. 77 Rothia , with a slightly lower relative abundance in the SSC group, has been reported to be increased in formula-fed infants in two studies (one study found the opposite) 80 and to be negatively associated with childhood asthma. 81 Lastly, Eubacterium hallii , reclassified as Anaerobutyricum soehngenii , 82 was lower in the SSC group.…”
Section: Discussionmentioning
confidence: 97%
“…This genus includes butyrate- and propionate-producing strains 75 and has been negatively associated with diarrheal cryptosporidiosis 76 and maternal stress. 77 However, the relationship with maternal stress was only present at 6 weeks and 3 months of age and reversed at 6 months of age. Flavonifractor , also higher in the SSC group, has been negatively associated with the development of asthma later in life 78 and was able to strongly suppress Th2 immune responses in mice.…”
Section: Discussionmentioning
confidence: 99%
“…Bifidobacterium pseudocatenulatum also plays a regulatory role in mediating the gut-brain axis ( 68 ). Interestingly, a recent study found that maternal psychosocial stress during pregnancy was associated with a reduced abundance of Bifidobacterium pseudocatenulatum in the infant gut microbiome ( 69 ). Clostridium innocuum and Clostridium neonatale are both gut commensals, but they can also be potential pathobionts ( 70 73 ).…”
Section: Discussionmentioning
confidence: 99%
“…[5]. Many authors suggest that the method of delivery plays a key role in this process [6]. It was found that infants born by caesarean section, as a rule, have more species of Staphylococcus, Bacillales, Propionobacterineae, Corynebacterineae, Firmicutes and Acinetobacter in the intestinal microflora, with fewer Actinobacteria and Bacteroidetes, while in the case of natural childbirth, increased colonization of the intestinal biotope Clostridium is revealed [7].…”
Section: Introduction 1general Aspects Of Gut Microbiotamentioning
confidence: 99%